Advancing Therapeutic Targets in IBD: Emerging Goals and Precision Medicine Approaches - Lucia Centanni; Clelia Cicerone; Fabrizio Fanizzi; Ferdinando D’Amico; Federica Furfaro; Alessandra Zilli; Tommaso Lorenzo Parigi; Laurent Peyrin-Biroulet; Silvio Danese; Mariangela Allocca (Pharmaceuticals)
Inflammatory bowel diseases (IBD) including Crohn’s disease (CD) and ulcerative colitis (UC) are chronic, relapsing conditions characterized by dysregulated immune responses and persistent intestinal inflammation. This review aims to examine new potential therapeutic targets in IBD starting from the STRIDE-II statements. Key targets now include clinical remission, endoscopic remission, and biomarker normalization (such as C-reactive protein and fecal calprotectin). Moreover, histologic remission, transmural remission, and in the future molecular targets are emerging as important indicators of sustained disease control. The treatment goals for inflammatory bowel disease are varied: to relieve symptoms, prevent permanent intestinal damage, promote inflammation remission, and minimize complications. Consequently, the therapeutic targets have evolved to become broader and more ambitious. Integrating these advanced therapeutic targets has the potential to redefine IBD management by promoting deeper disease control and improved patient outcomes. Further research is essential to validate these strategies and optimize their clinical implementation.